Effects of Astragalus Polysaccharides Nanoparticles on Cerebral Thrombosis in SD Rats - Sun, Qian; Shi, Pengqiang; Lin, Cuiling; Ma, Jing (Frontiers in Bioengineering and Biotechnology, 2020)
To investigate the efficacy and improvement of Astragalus polysaccharides (APS) and APS-nano on cerebral thrombosis in rats. Methods: A total of 72 SD rats were randomly divided into NC group, Model group, APS-Nano group, and APS group. The cerebral thrombosis Model of SD rats was established by injecting compound thrombus inducer into the internal carotid artery. After 14 days of different intervention treatments, the TTC staining of brain tissue were performed, and A/left brain wet weight ratio, left brain/right brain wet weight ratio, blood rheology indexes, and coagulation function indexes of cerebral thrombosis were measured. ELISA was used to measure the contents of thromboxane 2 (TXB2), 6-keto-prostaglandin F1α (6-Keto-PGF1α), tissue factor (TF), neuron-specific enolase (NSE), S-100β, catenin (CAT), superoxide dismutase (SOD), as well as malondialdehyde (MDA). The binding specificity between miR-885-3p and TF was verified by the double-luciferin reporting experiment, and western blot was used to measure the expression level of TF protein. Results: Compared with the Model group, after treatment with APS-nano or APS, the ratio of left brain/right brain wet weight decreased significantly. Whole blood low shear viscosity (WBLSV), whole blood high shear viscosity (WBHSV), plasma viscosity (PV), erythrocyte aggregation index (Arbc) was all reduced. In addition, prothrombin time (PT) and activated partial thromboplastin time (APTT) were increased, and fibrinogen (FIB) content was decreased. The expression of TXB2, 6-Keto-PGF1α, and TF showed a downward trend. Similarly, the expression of TF protein was decreased. Furthermore, the contents of NSE and S-100β proteins were all decreased, whereas the contents of CAT and SOD were increased, and the contents of MDA was decreased. At the same dose, compared with APS treatment, APS-nano treatment had a significant inhibitory effect on cerebral thrombosis in rats. Finally, we found that TF is a target gene of miR-885-3p and specifically binds to miR-885-3p. Conclusion: APS has a significant inhibitory effect on the formation of cerebral thrombosis induced by compound thrombus inducers. Moreover, APS-nano has a more significant inhibitory effect on cerebral thrombosis. Meanwhile, the regulation of miR-885-3p regulating TF expression may be related to the occurrence of cerebral thrombosis.